Phenolic compounds of laurus nobilis (review) - D. A. Konovalov; N. M. Alieva (Фармация и фармакология (Пятигорск), 2019)
One of the most famous plants of the laurel family (Lauraceae) is Laurus nobilis L.The aim of the study was to review scientific information on the study of phenolic compounds of wild-growing and cultivated Laurus nobilis L.Materials and methods. The study was performed using information retrieval (PubMed, ScholarGoogle) and library databases (eLibrary, Cyberleninca), as well as ResearchGate application for semantic search. The research methods are analysis and synthesis of the scientific literature data for the period from 2000 up to the present.Results. The data presented in the review show that leaves, fruits, and shoots of Laurus nobilis L. are valuable sources of phenolic compounds, such as phenolic acids, flavonoids, and proanthocyanidins. The quantitative content of these groups of substances varies depending on the collecting ground, the source of raw materials (cultivated or wild plants), the time (phase) of their harvesting, the method of drying, extraction from raw materials, etc. Phenolic compounds exhibit a pronounced antioxidant and antiradical activity, have an inhibitory effect on NO production, sodium-potassium adenosine triphosphatase, on tumour cell lines (HeLa, MCF7, NCI-H460 and HCT15), and are characterised by an antibacterial action against gram-positive and gram-negative bacteria.Conclusion. The analysis of the available scientific information showed that the phenolic compounds of Laurus nobilis L. are one of the main groups of the active compounds of this plant. The use of this information is essential for the development of new effective medicines based on the raw materials of Laurus nobilis L..